Forensic science : a sociological introduction - Lawless, Christopher (New York, NY : Routledge, 2022)
"Forensic Science provides a comprehensive overview of the sociology of forensic science. Drawing on a wealth of international research and case studies, it explores the intersection of science, technology, law and society and examines the production of forensic knowledge. The book explores a range of key topics such as: The integration of science into police work and criminal investigation The relationship between law and science Ethical and social issues raised by new forensic technology including DNA analysis Media portrayals of forensic science Forensic policy and the international agenda for forensic science This new edition has been fully updated, particularly with regard to new technology in relation to the various new forms of DNA technology and facial recognition. Updates and additions include: Facial recognition technology Digital forensics and its use in policing Algorithms (such as probabilistic genotyping) Genealogical searching Phenotyping This new edition also reviews and critically appraises recent scholarship in the field, and new international case studies have been introduced, providing readers with an international comparative perspective. Engaging with sociological literature to make arguments about the ways in which forensic science is socially constituted and shapes justice, Forensic Science provides an excellent introduction to students about the location of forensic science and the ways it fits within the criminal justice system, as well as systems of professionalisation and ethics. It is important and compelling reading for students taking a range of courses, including criminal investigation, policing, forensic science, and the sociology of science and technology"--
Revised edition of the author's Forensic science, 2016.
Includes bibliographical references and index.
Keywords: Forensic sciences; Crime -- Sociological aspects